24(S)‐hydroxycholesterol is actively eliminated from neuronal cells by ABCA1. (8th May 2013) - Matsuda, Akihiro; Nagao, Kohjiro; Matsuo, Michinori; Kioka, Noriyuki; Ueda, Kazumitsu
Abstract High cholesterol turnover catalyzed by cholesterol 24‐hydroxylase is essential for neural functions, especially learning. Because 24(S)‐hydroxycholesterol (24‐OHC), produced by 24‐hydroxylase, induces apoptosis of neuronal cells, it is vital to eliminate it rapidly from cells. Here, using differentiated SH‐SY5Y neuron‐like cells as a model, we examined whether 24‐OHC is actively eliminated via transporters induced by its accumulation. The expression of ABCA1 and ABCG1 was induced by 24‐OHC, as well as TO901317 and retinoic acid, which are ligands of the nuclear receptors liver X receptor/retinoid X receptor (LXR/RXR). When the expression of ABCA1 and ABCG1 was induced, 24‐OHC efflux was stimulated in the presence of high‐density lipoprotein (HDL), whereas apolipoprotein A‐I was not an efficient acceptor. The efflux was suppressed by the addition of siRNA against ABCA1, but not by ABCG1 siRNA. To confirm the role of each transporter, we analyzed human embryonic kidney 293 cells stably expressing human ABCA1 or ABCG1; we clearly observed 24‐OHC efflux in the presence of HDL, whereas efflux in the presence of apolipoprotein A‐I was marginal. Furthermore, the treatment of primary cerebral neurons with LXR/RXR ligands suppressed the toxicity of 24‐OHC. These results suggest that ABCA1 actively eliminates 24‐OHC in the presence of HDL as a lipid acceptor and protects neuronal cells.